Therapeutic applications of ursolic acid: a comprehensive review and utilization of predictive tools - Sherien M. Bakry; Riham A. El-Shiekh; Shymaa Hatem; Asmaa A. Mandour; Ahmed M. El-Dessouki; Abeer Bishr; Heba Elosaily; Ahmed F. Mohamed; Shaza M. Elhusseiny (Future Journal of Pharmaceutical Sciences)
Abstract Background Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder affecting women of reproductive age, characterized by a range of metabolic and reproductive complications, including insulin resistance, hyperandrogenism, and menstrual irregularities. The complexity of PCOS necessitates innovative therapeutic strategies that extend beyond conventional pharmacological treatments. Main body Ursolic acid (UA), a natural pentacyclic triterpenoid found in various plants, has gained significant attention for its diverse pharmacological properties including anti-inflammatory, antioxidant, anticancer, antidiabetic, antimicrobial, antihyperlipidemic, anti-obesity, neuroprotective, hepatoprotective, and cardioprotective activities. Additionally, the integration of predictive tools, such as artificial intelligence and bioinformatics databases like STRING (Search Tool for the Retrieval of Interacting Genes/Proteins) and KEGG (Kyoto Encyclopedia of Genes and Genomes), allows for the identification of key protein targets and pathways influenced by UA, including TP53 (Tumor Protein P53), AR (Androgen Receptor), ESR1 (Estrogen Receptor 1), BCL2 (B-cell Lymphoma 2), STAT3 (Signal Transducer and Activator of Transcription 3), and IL6 (Interleukin 6). These pathways are crucial for inflammatory regulation and have been linked to the symptoms of PCOS. Further in silico studies were conducted to validate these findings, highlighting the need for additional preclinical and clinical research. Conclusion Comprehensive guidelines for the effective use of UA in managing PCOS are warranted to ensure optimal treatment strategies.